2015
DOI: 10.1080/13607863.2015.1056770
|View full text |Cite
|
Sign up to set email alerts
|

Positive attitude toward life, emotional expression, self-rated health, and depressive symptoms among centenarians and near-centenarians

Abstract: Objectives Favorable attitudes, emotions, personality characteristics, and self-rated health have been associated with successful aging in late life. However, less is known regarding these constructs and their relationships to mental health outcomes in the oldest old persons. This study examined cross-sectional relationships of these psychological factors to depressive symptoms in centenarians and near-centenarians. Methods A selected sample of Ashkenazi Jewish older adults ages 98 to 107 (n = 54, 78% female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 79 publications
8
34
0
2
Order By: Relevance
“…This finding is similar to that of previous studies, in that better subjective health has been reported to be an important factor influencing older adults’ QoL (Kato et al. ), and good subjective health may help to reduce depressive moods among older adults (Reyes Fernández et al. ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to that of previous studies, in that better subjective health has been reported to be an important factor influencing older adults’ QoL (Kato et al. ), and good subjective health may help to reduce depressive moods among older adults (Reyes Fernández et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Although, to older adults, having objectively good health is important, their subjective health status serves as an important indicator of their overall health (Meng & D'Arcy 2014;Vaillant & Wolff 2012). This finding is similar to that of previous studies, in that better subjective health has been reported to be an important factor influencing older adults' QoL (Kato et al 2016), and good subjective health may help to reduce depressive moods among older adults (Reyes Fern andez et al 2016).…”
Section: The Association Of Independent Variables With Sasupporting
confidence: 85%
“…Moreover, there was no significant SRH moderation on age groups and gender in reporting NCD (Table ). This supports our proposal that people with high SRH may have a more positive attitude or perception towards their general health and well‐being . They may also be more actively involved in using healthcare resources and more attuned to health promotions and therefore seek help to maintain or improve their current health status or condition .…”
Section: Discussionsupporting
confidence: 84%
“…This supports our proposal that people with high SRH may have a more positive attitude or perception towards their general health and well‐being . They may also be more actively involved in using healthcare resources and more attuned to health promotions and therefore seek help to maintain or improve their current health status or condition . People with high SRH may be more willing to accept the overall benefit of medicines because they consider the necessity of their medication as being greater than their concerns about their medication, resulting in higher NCD reporting.…”
Section: Discussionsupporting
confidence: 80%
“…Although, limited by its cross-sectional design, findings suggest these psychological factors may exert protective effects on mental health outcomes in advanced age [53].…”
Section: Psychological Attitudementioning
confidence: 99%